Mitigation behaviour analysis to understand the effectiveness of COVID-19 infection control policies in Riau - Dendy Kharisna; Rizka Febtrina; Sri Yanti; Bayu Azhar; Wardah; Angga Arfina (Journal of the Pakistan Medical Association, 2024)
Objective:To analyse mitigation behaviour in understanding the effectiveness of coronavirus disease-2019 infection control programme. Method:The quantitative, descriptive study was conducted in the Riau province of Indonesia from April to May 2020. After approval from the Faculty of Medicine, Riau University, and comprised individuals of either gender aged 15-69 years. Data was collected using a closed questionnaire generated on Google Forms and distributed through social media using WhatsApp. Data was analysed using SPSS 27. Results: Of the 440 subjects, 304(69.1%) were women, 185(42%) were in the late adolescent age group, and 345(78.4%) had education up to the college level. The mitigation behaviour was appropriate in 263(59.8%) cases at the individual level and 233(53%) at the community level. Conclusion: The mitigation behaviour towards coronavirus disease-2019 infection prevention was appropriate in majority of the subjects at both individual and community levels. Keywords: Adolescent, Infection Control, COVID-19.